The relationship between creative thinking and environmental awareness among sixth grade students )A field study in Lattakia) - منون, ولاء نضال (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The aim of the research is to define the level of creative thinking among sixth-graders in Lattakia, to define their level of environmental awareness, and to define the relationship between creative thinking and environmental awareness of the research sample. To achieve this goal, the descriptive approach was used, and the Torrance Test was applied in its formal form (B). The environmental awareness test was prepared by the researcher on 140 sixth-grade students. The research reached several results, namely: -The level of creative thinking with its skills (fluency, flexibility, originality, details) of the research sample was low. -The level of environmental awareness with its dimensions (the cognitive dimension, the emotional dimension, the behavioral dimension) among the research sample was low. -There is a statistically significant correlation relationship between students' scores on the creative thinking test and their scores. In light of the research results, the following may be suggested: -Enriching the curricula with programs and activities that develop students' creative skills, and open opportunities for them to express their creative abilities by following methods based on dialogue and discovery. -Increasing environmental issues within the curricula, and focusing teachers' attention on raising the level of environmental awareness among students by assigning them to activities aimed at preserving the environment.